(untitled) (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2022)
Quality control is the most important factor in increasing product quality productivity for any company. Quality control is carried out so that there are no defects in the production process, so that it has good product quality standards. One of the causes of production defects is room temperature. The method used to determine the relationship between room temperature and the number of production defects is simple linear regression analysis. From the calculation results, there is a significant effect of room temperature on the number of production defects.